Dynamics of a Stage-Structured-Prey and Predator Model with Linear Harvesting of Mature Prey and Predator - Haque, Md. Manarul; Sarwardi, Sahabuddin (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper we have studied the dynamical behaviors of stage-structured-prey and predator model with linear harvesting of both mature prey and predator. Optimal harvesting policy, positivity, boundedness and Hopf-bifurcation have been studied. Finally, some graphical and numerical simulations are given in order to validate our analytical and theoretical findings.